Influence of de-structured starch on fine-stranded polymeric and coarse-stranded particulate whey protein gels. (February 2023) - Ang, Cai Ling; Matia-Merino, Lara; Lim, Kaiyang; Goh, Kelvin Kim Tha
Abstract: This study investigated the phase stability of liquid mixtures and composite gels properties of de-structured waxy potato starch (DWPS) and whey protein isolate (WPI). The DWPS are physically-modified starches treated at 120, 140 and 150 °C for 30 min under constant shear. The composite gels (13% w/w WPI and 4% w/w DWPS) characteristics at pH 7 and pH 5 were evaluated based on their mechanical properties, microstructure, and water-immersion stability. At pH 7, the addition of DWPS did not result in any phase separation. Synergistic gel hardness of WPI was obtained with incorporation of 140 °C DWPS likely due to the enhanced density of a very fine-stranded gel network. The ability of the gel to retain its shape when immersed in water for 40 h was prominent for composite gels containing either gelatinised starch (control) or DWPS samples. In contrast, pure WPI gels and composite gels containing maltodextrin appeared fluid-like and disintegrated gels, respectively. At pH 5, the addition of gelatinised starch or DWPS weakened the particulate protein gels, likely due to phase separation and interrupted protein network with starch polymers acting as an inactive filler. A logarithmically decline in gel hardness was noted as the molar mass of DWPS increased. The coarse porous structure of particulate gels exhibited poor water-holding capacity, low water absorption, and high degree of starch leaching. However, the higher molar mass DWPS polymers enhanced the water-holding capacity of the gels and reduced their own diffusivity from the gel network. Graphical abstract: Image 1 Highlights: 140 °C DWPS synergistically enhanced the polymeric gel network of WPI. WPI + DWPS polymeric gels had good shape retention after 40 h water immersion. Particulate WPI gel strength decreased with increasing molar mass of DWPS samples. DWPS in particulate WPI gel existed as an inactive filler. Large molar mass DWPS could disrupt the connectivity of particulate WPI gels.